Daily tenofovir disoproxil fumarate/emtricitabine and hydroxychloroquine for pre-exposure prophylaxis of COVID-19: a double-blind placebo-controlled randomized trial in healthcare workers. (January 2023) - Polo, Rosa; García-Albéniz, Xabier; Terán, Carolina; Morales, Miguel; Rial-Crestelo, David; Garcinuño, M. Angeles; García del Toro, Miguel; Hita, César; Gómez-Sirvent, Juan Luis; Buzón, Luis; Díaz de Santiago, Alberto; Arellano, Jose Pérez; et al.
Abstract: Objectives: To assess the effect of hydroxychloroquine (HCQ) and Tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) as pre-exposure prophylaxis on COVID-19 risk. Methods: EPICOS is a double-blind, placebo-controlled randomized trial conducted in Spain, Bolivia, and Venezuela. Healthcare workers with negative SARS-CoV-2 IgM/IgG test were randomly assigned to the following: daily TDF/FTC plus HCQ for 12 weeks, TDF/FTC plus HCQ placebo, HCQ plus TDF/FTC placebo, and TDF/FTC placebo plus HCQ placebo. Randomization was performed in groups of four. Primary outcome was laboratory-confirmed, symptomatic COVID-19. We also studied any (symptomatic or asymptomatic) COVID-19. We compared group-specific 14-week risks via differences and ratios with 95% CIs. Results: Of 1002 individuals screened, 926 (92.4%) were eligible and there were 14 cases of symptomatic COVID-19: 220 were assigned to the TDF/FTC plus HCQ group (3 cases), 231 to the TDF/FTC placebo plus HCQ group (3 cases), 233 to the TDF/FTC plus HCQ placebo group (3 cases), and 223 to the double placebo group (5 cases). Compared with the double placebo group, 14-week risk ratios (95% CI) of symptomatic COVID-19 were 0.39 (0.00–1.98) for TDF + HCQ, 0.34 (0.00–2.06) for TDF, and 0.49 (0.00–2.29) for HCQ. Corresponding risk ratios of any COVID-19 were 0.51 (0.21–1.00) for TDF + HCQ, 0.81 (0.44–1.49) for TDF, and 0.73 (0.41–1.38) for HCQ. Adverse events were generally mild. Discussion: The target sample size was not met. Our findings are compatible with both benefit and harm of pre-exposure prophylaxis with TDF/FTC and HCQ, alone or in combination, compared with placebo.